Investigating the cryoprotective efficacy of fructans in mammalian cell systems via a structure-functional perspective - Tornaci, Selay; Erginer, Merve; Gokalsin, Baris; Aysan, Arzu; Cetin, Metin; Sadauki, Mubarak; Findikli, Necati (Elsevier Sci Ltd, 2024)
Fructans have long been known with their role in protecting organisms against various stress factors due to their ability to induce controlled dehydration and support membrane stability. Considering the vital importance of such features in cryo-technologies, this study aimed to explore the cryoprotective efficacy of fructans in mammalian cell systems where structurally different fructan polymers were examined on in vitro cell models derived from organs such as the liver, frequently used in transplantation, osteoblast, and cord cells, commonly employed in cell banking, as well as human seminal fluids that are of vital importance in assisted reproductive technology. To gain insights into the fructan/membrane interplay, structural differences were linked to rheological properties as well as to lipid membrane interactions where both fluorescein leakage from unilamellar liposomes and membrane integrity of osteoblast cells were monitored. High survival rates obtained with human endothelial, osteoblast and liver cells for up to two months clearly showed that fructans could be considered as effective non-permeating cryoprotectants, especially for extended periods of cryopreservation. In trials with human seminal fluid, short chained levan in combination with human serum albumin and glycerol proved very effective in preserving semen samples across multiple patients without any morphological abnormalities.
Keywords: Cryopreservation; Cryoprotectant; Fructan; Levan; Inulin